Aggressive primary urethral malignancy masquerading as stricture urethra: Unusual presentation of a rare malignancy - Parnandi, Sridhar; Varma, Ravindra G; Saple, Amit (Indian Journal of Case Reports, 2021)
Bladder outlet obstruction in an elderly male patient is most of the time diagnosed as prostatomegaly or stricture urethra unless there is a high index of suspicion for other differential diagnoses. Rare tumors like urethral malignancy may be misdiagnosed due to their varied and delayed mode of presentation. Here, we present a case of a patient who presented with acute urinary retention and was suspected to be a stricture urethra which ultimately turned out to be an aggressive urethral tumor. Investigations such as retrograde urethrogram, ultrasound, or cystoscopy which are the most common diagnostic modalities in a patient with lower urinary tract symptoms may not diagnose urethral tumors. Delayed diagnosis is common in these tumors resulting in a lesser chance for curative treatment. A high index of suspicion with a lesser threshold for investigations like MRI is pivotal for early diagnosis in these patients.